Unveiling the positive effect of mineral induced natural organic matter (NOM) on catalyst properties and catalytic dechlorination performance: An experiment and DFT study. (15th August 2022) - P, Anil Kumar Reddy; Senthamaraikannan, Thillai Govindaraja; Lim, Dong-Hee; Choi, Minhee; Yoon, Sunho; Shin, Jaegwan; Chon, Kangmin; Bae, Sungjun
Highlights: Effect of Z-NOM (contain in natural zeolite) on Ni/Fe bimetal catalyst was studied. Z-NOM enhanced the aerobic stability, dispensability and mobility of NF@NZ. Z-NOM improved TCE and H2 adsorption on Ni/Fe bimetal for rapid TCE degradation. By-product analysis confirmed ethane as final product and ethylene as intermediate. DFT proved that Z-NOM boosts charge density on Ni/Fe for strong H2 /TCE adsorption. Abstract: Herein, we report the significant effects of natural organic matter contained in natural zeolite (Z-NOM) on the physicochemical characteristics of a Ni/Fe@natural zeolite (NF@NZ) catalyst and its decontamination performance toward the dechlorination of trichloroethylene (TCE). Z-NOM predominantly consists of humic-like substances and has demonstrable utility in the synthesis of bimetallic catalysts. Compared to NF@NZ600C (devoid of Z-NOM), NF@NZ had increased dispersibility and mobility and showed significant enhancement in the catalytic dechlorination of TCE owing to the encapsulation of Ni 0 /Fe 0 nanoparticles by Z-NOM. The results of corrosion experiments, spectroscopic analyses, and H2 production experiments confirmed that Ni 0 acted as an efficient cocatalyst with Fe 0 to enhance the dechlorination of TCE to ethane, and Z-NOM-capped Ni 0 showed improved adsorption of TCE and atomic hydrogen on their reactive sites and oxidation resistance. The density functional theory (DFT) studies have substantiated the improved adsorption of TCE due to the presence of NOM (especially by COOH structure) and the enhanced charge density at the Ni site in the Ni/Fe bimetal alloy for the stronger adsorption of hydrogen atoms that ultimately enhanced the TCE reduction reaction. These findings illustrate the efficiency of NOM containing natural minerals toward the synthesis of bimetallic catalysts for practical applications. Graphical abstract: Image, graphical abstract